Predictors of Dysmenorrhea and Its Impact on Quality of Life among Tribal Adolescent Girls in India - Udayar, Sharvanan E; Jeeragyal, Devika P; Kruthika, K (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
Many girls are faced with the challenge of Dysmenorrhea during their adolescent years. Therefore, this study aimed at finding the prevalence of Dysmenorrhea, its risk factors, and its impact on quality of life among teenage girls residing in tribal welfare hostels. After obtaining informed consent, a cross-sectional survey was conducted among 582 adolescent girls residing in tribal welfare hostels in southern India. Data was collected by purposive sampling technique, and the mean, standard deviation and percentages, and frequencies were applied for summarizing the continuous and quantitative variables. Additionally, multinominal regression analysis was performed to determine the factors associated with Dysmenorrhea. The results indicated the prevalence of Dysmenorrhea was 58.4%, while 48.8% of participants reported physical premenstrual symptoms. Furthermore, there is a significant association between those experiencing moderate to severe pain and Dysmenorrhea (p<0.000). Association between factors such as prolonged menstrual duration [AOR,3.4(95%CI,1.49-7.81)], those having moderate [AOR,5.78(95% CI,1.96-17.02)] to severe menstrual bleeding [AOR, 5.1 (95% CI, 1.78-14.08)], family history [AOR, 3.5 (95%CI,2.30-5.54)]and somatic symptoms [AOR,2.03 (95%CI, 1.33-3.08] were statistically significant. In conclusion, Dysmenorrhea had a significant impact on quality of life since the girls could not attend routine activities. Therefore, incorporating reproductive health issues in education programs will encourage treatment-seeking behavior among the girls.